Edukasi dan Pendampingan Pola Asuh Orang Tua dalam Meningkatkan Tumbuh Kembang dan Kemandirian Anak di TPA Athahira Pendowoharjo, Bantul: - Prihastuti (Jurnal Kesehatan Pengabdian Masyarakat (JKPM), 2024)
Early childhood growth, development, and independence remain critical public health concerns, with parenting practices identified as a key determinant. This community service program aimed to enhance parents’ knowledge and skills in applying appropriate parenting practices to support children’s development and independence at TPA Athahira Pendowoharjo. The intervention employed a community-based participatory approach through education sessions, interactive discussions, and practical demonstrations. The participants consisted of 20 parents of early childhood children. Evaluation was conducted using pretest–posttest assessments and behavioral observations. The results demonstrated an improvement in parents’ knowledge regarding parenting practices and child development stimulation, as well as initial behavioral changes, particularly in encouraging children’s independence. Baseline findings also indicated that a proportion of children had limited independence in daily activities, which was associated with prior parenting practices. This program contributed to improving parental health literacy and strengthening the role of families in supporting optimal child development. Therefore, community-based parenting education and mentoring represent an effective promotive and preventive strategy to enhance early childhood development outcomes.